Implementasi Pembelajaran Berbasis Steam Melalui Kegiatan Ecoprint Pada Anak Usia 5–6 Tahun Di TK FII Mardhotillah - Alfika Nabila; Dindin Abdul Muiz Lidinillah; Qonita Qonita (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Science, Technology, Engineering, Art, and Mathematics (STEAM)-based learning requires learning activities that provide direct learning experiences for young children. One activity with the potential to support the implementation of STEAM-based learning is ecoprint. This study aimed to describe the implementation of STEAM-based learning through ecoprint activities for children aged 5–6 years at TK Fii Mardhotillah. This study employed a qualitative method with a descriptive approach. The participants consisted of one classroom teacher and ten children aged 5–6 years from Group B1. Data were collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña model, including data condensation, data display, and conclusion drawing. The findings revealed that the implementation of STEAM-based learning through ecoprint activities demonstrated the Science aspect through observing the characteristics of natural materials, Technology through the use of simple tools and materials, Engineering through arranging, testing, and refining the artwork, Art through creating artwork based on children's ideas, and Mathematics through introducing the concepts of shape, size, and sequence, which were integrated through scaffolding activities within the learning process. Ecoprint activities also provided opportunities for children to actively engage in exploration, decision-making, and simple problem-solving throughout the learning process. Therefore, within the context of this study, ecoprint has the potential to serve as an alternative approach for implementing STEAM-based learning in early childhood education.